2024
DOI: 10.3389/fnmol.2023.1332348
|View full text |Cite
|
Sign up to set email alerts
|

Molecular pathways underlying sympathetic autonomic overshooting leading to fear and traumatic memories: looking for alternative therapeutic options for post-traumatic stress disorder

Márcia Azevedo,
Raquel Martinho,
Ana Oliveira
et al.

Abstract: The sympathoadrenal medullary system and the hypothalamic-pituitary-adrenal axis are both activated upon stressful events. The release of catecholamines, such as dopamine, norepinephrine (NE), and epinephrine (EPI), from sympathetic autonomic nerves participate in the adaptive responses to acute stress. Most theories suggest that activation of peripheral β-adrenoceptors (β-ARs) mediates catecholamines-induced memory enhancement. These include direct activation of β-ARs in the vagus nerve, as well as indirect r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 155 publications
0
0
0
Order By: Relevance
“…It was shown that at the moment of trauma, molecular cascades involved in the development of NMDA-dependent long-term potentiation are activated in the hippocampus and amygdala [ 44 , 45 , 46 ]. An increase in the phosphorylation level of CREB (calcium-response element binding protein) during trauma was also demonstrated [ 47 , 48 , 49 ], along with the activation of gene expression related to memory consolidation [ 26 , 50 , 51 ]. Meanwhile, administering kinase inhibitors involved in memory consolidation at the moment of trauma reduces the likelihood of developing PTSD in animals [ 2 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that at the moment of trauma, molecular cascades involved in the development of NMDA-dependent long-term potentiation are activated in the hippocampus and amygdala [ 44 , 45 , 46 ]. An increase in the phosphorylation level of CREB (calcium-response element binding protein) during trauma was also demonstrated [ 47 , 48 , 49 ], along with the activation of gene expression related to memory consolidation [ 26 , 50 , 51 ]. Meanwhile, administering kinase inhibitors involved in memory consolidation at the moment of trauma reduces the likelihood of developing PTSD in animals [ 2 , 52 ].…”
Section: Discussionmentioning
confidence: 99%